Simulation of common rail for hydrogen engine in automobile application - Muhammad Hamizi, Msduki (2010)
This project is about to develop common rail model for hydrogen engine. The objective of the project is firstly to develop simulation model for common rail hydrogen engine. Secondly to simulate common rail hydrogen engine for determining the best parameters. Thirdly to improve the efficiency of the common rail. This project is conducted in five stages, which is develop a simple common rail system, change the simulation analysis from using gasoline as its fuel to hydrogen gas, change the rail diameter of common rail, change the rail pressure and lastly, change the injector hole diameter. Performance output is evaluated in five criteria, which are the pressure in pipe, speed of sound in pipe, mass flow rate in pipe, pressure in injector connecter and mass flow rate in injector connector. From the simulation analysis, it can conclude that common rail model have been developed with suitable parameter for hydrogen gas as the fuel. Even though the exact dimension of parameters is not state clearly, it s already give the range value of dimension to get the best parameters. Therefore, it is suggested that Parameter Identification Technique is utilized in this project to determine the more accurate dimension for common rail in hydrogen engine.